The biomechanics of back pain: what we know so far - Adams, Michael (Henry Stewart Talks, 2015)
Spinal anatomy, Where back pain comes from, Forces acting on the spine, Mechanisms of injury to the lumbar spine, Predisposition to injury: “vulnerable” tissues, Spinal degeneration, “Functional pathology”